PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP AKTIVITAS BELAJAR SISWA KELAS V SDN TEMBOK DUKUH III SURABAYA - Nayla Zulfia; Prastyo, Danang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to determine the effect of the PBL model on the learning activities of fifth-gradestudents at SDN Tembok Dukuh III Surabaya. This research is experimental in nature. The sampleconsists of students from classes V-A and V-B, while the population consists of all fifth-grade students at SDN Tembok Dukuh III Surabaya. The Postest OnlyNonequivalent Control Group Design is the quasi-experimental design used in this study. SPSS software was used to analyze the data. Data analysis showsthat the PBL model has an impact on the learningactivities of fifth-grade students at SDN Tembok Dukuh III Surabaya.